Pengaruh Lokasi Pesantren, Biaya Pendidikan, Kualitas Layanan Terhadap Keputusan Memilih Pesantren Kampus Ainul Yaqin Universitas Islam Malang (Study Kasus pada Santri dan Santriwati Pesantren Kampus Ainul Yaqin Universitas Islam Malang Angkatan 2019-2022) - Atika Nuzulil Laili; N Rachma; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The purpose of this research was to determine and analyze the effect of the location of the Islamic boarding school, the cost of education, the quality of service on the decision to choose a Islamic boarding school at Ainul Yaqin Campus, Islamic University of Malang. The data source for this research is primary data obtained from answering statements at the time of distributing questionnaires to students and female students at the Islamic Boarding School, Ainul Yaqin Campus, Islamic University of Malang, Class of 2019-2022. The sample method used is purposive sampling with the slovin formula. The number of samples in this study were 100 respondents. The dqta analysis method uses instrument test, normality test, classical assumption test, multiple linear regression analysis, hypothesis testing and coefficient of determination test. The results showed: (1) the location of the Islamic boarding school, the cost of education, the quality of service had a simultaneous and significant effect on the decision to choose the Ainul Yaqin Campus Islamic Boarding School, Islamic University of Malang, (2) the location of the Islamic boarding school had a positive and significant effect on the decision to choose the Ainul Yaqin Campus Islamic Boarding School, Islamic University of Malang , (3) the cost of education has a positive and significant effect on the decision to choose the Ainul Yaqin Campus Islamic Boarding School, Islamic University of Malang, (4) the quality of service has a positive and significant effect on the decision to choose the Ainul Yaqin Campus Islamic Boarding School, Islamic University of Malang. Keywords: Location,Cost Education, Quality of Sevice